Mangongkal Holi: Upacara Adat Yang Mencerminkan Nilai-Nilai Kehidupan - Afifah, Tengku; Muhammad Zidan Hakim; Santriana Sigalingging; Gustianingsih (CENDERAWASIH: Jurnal Antropologi Papua, 2024)
The Mangongkal Holi tradition is one of the cultures that developed in the midst of the life of the Toba Batak community and at the same time made it a distinctive tradition of the Toba Batak tribe. The Mangongkal Holi tradition is closely related to a ritual ceremony that has sacred value and is believed by the Toba Batak community. The procession of this ceremony must go through several stages and also involve the extended family of the followers of this tradition. The author is interested in describing and knowing what are the life values that occur in the Toba Batak community contained in the Mangongkal Holi tradition. The existence of a nature of respecting ancestors has been embedded in the Toba Batak community making this tradition very relevant to this. The purpose of this writing is to find out what are the values of life in the Toba Batak community contained in the Mangongkal Holi tradition. This research method is a qualitative method by analyzing descriptive data. The author uses written and oral sources such as books, articles, previous writings and also interviews. This paper is expected to increase public insight into the understanding of Toba Batak cultural values in Mangongkal Holi so that it continues to exist in the future.